Numerical investigation of the performance and soil temperature recovery of an EATHE system under intermittent operations. (September 2016) - Mathur, Anuj; Surana, Ankit Kumar; Mathur, Sanjay
Abstract: One of the problems in operating earth air tunnel heat exchangers (EATHE) for cooling in summer, with soil having high specific heat and low moisture content is accumulation of heat around the pipe. The low rate of heat dissipation due to conduction restricts the performance of EATHE over subsequent years. In the present paper, numerical simulations have been performed to investigate the thermal performance and soil temperature during summer operation in Jaipur to estimate extent of soil degradation. The simulation result indicates that by the end of summer, the soil leads to thermal saturation which in turn, may render it unusable for next summer. This scenario demands for heat removal through force convection. Three strategies namely, night purging during summer operation, day operation during winter and night operation during winter were attempted to estimate extent of soil recovery. Simulation results show that the average COPs for summer, summer with night purging, winter day and winter night operation mode are 4.23, 3.68, 5.01, and 6.65 respectively. It was found that advantage of night purging is less than energy required to run blower for night purging. However, winter day/night operation offers space heating and better soil for next summer. Highlights: We estimated extent of soil degradation and regeneration in intermittent operation modes. The transient CFD model of EATHE systems was developed and validated. Low rate of heat dissipation due to conduction restricts the performance of EATHE over subsequent years. Three operational strategies were attempted to estimate soil recovery through force convection. It was found that winter day/night operations offers space heating and lower soil temperature for next summer.